PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI HUMAN TRAFFICKING PADA KASUS ONLINE SCAM DI INDONESIA - Nadya, Sylvie; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Human trafficking through online scam schemes has emerged as a new form of transnational crime that is increasingly prevalent in Southeast Asia, including Indonesia. Thousands of Indonesian citizens have fallen victim to fake job offers spread through social media, lured by promises of high salaries and simple recruitment processes. However, upon arrival abroad, these individuals are instead subjected to exploitative working conditions in companies operating online scam activities. This research aims to analyze the role of the International Organization for Migration (IOM) in addressing human trafficking in online scam cases in Indonesia. This research uses qualitative method with primary data collected through interviews and secondary data through literature review. The researcher further utilizes group behavior level of analysis, the pluralist perspective, and Clive Archer’s theory of International Organizations. The result of this study indicate that IOM carries out its role through the 3P + Partnership approach: Prevention, Protection, Prosecution, and Partnership. This framework comprehensively illustrates IOM’s efforts in responding to the increasingly complex issue of human trafficking, which has evolved in line with advances in digital technology, particularly in the form of online scams. Keywords : IOM, Human Trafficking, Online Scam, International Organizations